Corruption and government revenue: Evidence of a non-linear relationship driven by crises - Željko Bogetić; Dominik Naeher (Journal of Applied Economics, 2024)
A large body of literature studies the relationship between corruption and economic outcomes, including government revenue mobilization, but there is little evidence on how this relationship changes during times of crisis. Using a comprehensive panel dataset covering up to 194 countries in the period 1996 to 2020, we find evidence of a negative link between corruption and revenue that is amplified in times of crisis. The amplification appears to be driven by countries with lower average income levels, non-democratic governments, and higher natural resource dependency. Our findings are helpful in assessing different views of corruption offered in the literature. Overall, we find our results to be more consistent with a rent seeking view of corruption whereby, in times of crisis, corruption becomes more pervasive and government revenue declines. In contrast, we find no empirical support for the view that crises represent times of social improvement associated with increases in revenues.
Keywords: 330; Corruption; crisis; government revenue; rent seeking